FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREMENSTRUAL SYNDROME PADA SISWI KELAS IX SMPN 13 PURWOREJO DI KECAMATAN KUTOARJO KABUPATEN PURWOREJO - Kusumaningsih, Tri Puspa; Chandra Wulandari, Fetty; Nugraheni, Devi (Jurnal Komunikasi Kesehatan, 2023)
Premenstrual syndrome is a collection of physical, psychological, and emotional symptoms associated with a woman's menstrual cycle and consistently occurs during the luteal stage of the menstrual cycle due to hormonal changes associated with the cycle during ovulation (release of eggs from the ovaries) and menstruation. SMPN 13 Purworejo in grade ix students on December 21, 2021, out of 63 students, 56 had premenstrual syndrome and 7 did not have premenstrual syndrome. Research Objectives This study aims to determine the factors associated with the incidence of premenstrual syndrome in class ix students of SMPN 13 Purworejo. Research Metodology This type of research is correlative, cross sectional approach. The sample is 93 total sampling techniques. Closed questionnaire data collection. Chi-Square test analysis technique. Research time April 2022. Research Results There is a relationship between genetic factors (p value = 0.000), there is no relationship between age factors (p value = 0.441), there is no relationship between nutritional status factors (p value = 0.172).